2003
DOI: 10.1021/ja029665m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Binding and Efficient Cellular Uptake of Guanidine-Based Peptide Nucleic Acids (GPNA)

Abstract: Incorporation of a guanidine functional group into the PNA backbone facilitates cellular uptake of PNA into mammalian cells with efficiency comparable to that of the TAT transduction domain. The modified PNA recognizes and binds to the complementary DNA strand in accordance with Watson-Crick recognition rules. However, unlike polypyrimidine PNA which binds to DNA in 2:1 stoichiometry, the modified PNA binds to complementary DNA in a 1:1 ratio to form a highly stable duplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
154
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(157 citation statements)
references
References 14 publications
3
154
0
Order By: Relevance
“…However, poor cellular uptake of PNA has been a major impediment in the development of this class of compounds as therapeutic agents. Various approaches have been adopted for the ef cient biodelivery of PNA into cells, including conjugation to lipophilic moieties (Ljungstrom et al, 1999;Muratovska et al, 2001), cell-speci c receptor ligands (Basu and Wickstrom, 1997;Boffa et al, 2000;Zhang et al, 2001), carrier peptides (Cutrona et al, 2000), neamine (Riguet et al, 2004), and guanidine-based PNA (Zhou et al, 2003) electrostatically bound with the polymeric core shell microsphere (Chiarantini et al, 2005) or loaded into the autologous red blood cells (Chiarantini et al, 1995;Turrini et al, 1991). We have demonstrated that polyamide nucleic acids complementary to the transactivation response (TAR) element of HIV-1 LTR inhibit HIV-1 production when transfected in HIV-1 infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor cellular uptake of PNA has been a major impediment in the development of this class of compounds as therapeutic agents. Various approaches have been adopted for the ef cient biodelivery of PNA into cells, including conjugation to lipophilic moieties (Ljungstrom et al, 1999;Muratovska et al, 2001), cell-speci c receptor ligands (Basu and Wickstrom, 1997;Boffa et al, 2000;Zhang et al, 2001), carrier peptides (Cutrona et al, 2000), neamine (Riguet et al, 2004), and guanidine-based PNA (Zhou et al, 2003) electrostatically bound with the polymeric core shell microsphere (Chiarantini et al, 2005) or loaded into the autologous red blood cells (Chiarantini et al, 1995;Turrini et al, 1991). We have demonstrated that polyamide nucleic acids complementary to the transactivation response (TAR) element of HIV-1 LTR inhibit HIV-1 production when transfected in HIV-1 infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, many modifications of the original PNA backbones have been proposed in order to improve performances in term of affinity and specificity. Modification of the PNA backbone with positively charged groups (figure 4) has also been demonstrated to enhance cellular uptake and consequently PNA efficiency , Zhou et al, 2003. Although the steric requirements for binding RNA have not been extensively studied so far, the availability of different chemical strategies to design and synthesize PNA analogues is the basis for the development of new peptide nucleic acids (PNAs) specifically aimed at targeting RNA, to be used for miR targeting.…”
Section: Modified Pnas Can Improve Mir Targetingmentioning
confidence: 99%
“…In efforts to improve upon these limitations, several different types of synthetic molecular transporters (MTs), e.g. peptoids, 6 oligocarbamates, 7 ÎČ-peptides, 8 peptide nucleic acids, 9 and others [10][11][12][13] have been investigated. Recently we have explored novel classes of synthetic molecular transporters, in which multiple units of the guanidine functionality are attached through linear or branched chain carboxylate linkers to various scaffolds such as inositol dimers, sorbitol, lactose, and sucrose.…”
Section: Introductionmentioning
confidence: 99%